Pengujian Power Theory pada Skema Remunerasi Pimpinan Puncak Perusahaan Publik di Indonesia - Ramadhanti, Wita; Indrayanto, Adi (Jurnal Aplikasi Manajemen, 2016)
This study examined the impact of the Firm characteristics and the investmen opportunity set against executive remuneration. This study also explained the role of institutional ownership in moderating the relationship between firm size, sales and growth of the cash compensation. Data was taken from a listed company in Indonesia Stock Exchange 2011-2014 which has an executive compensation data in Swa Magazine survey.The compensation data are taken from Survey conduct by Swa Magazines, not directly from annual and financial reports. This is because very few Indonesian public companies that explicitly stated their remunerations in Annual Reports or Financial Reports. Investor could have additional information to invest in stock market. Data were analyzed using OLS Regression. A Company is fundamentally good and a trusted is a company that has an assets, sales, and high managerial compensation, but has a majority of institutional ownership of the total ownership structure. This study used institutional ownership as a moderating variable not managerial ownership such as in previous studies.That wascaused by the capital market condition in Indonesia as the concentration of institutional ownership is higher than the market or management. The results showed that the firm characteristics has an effectto the company's executive remuneration. Furthermore, institutional ownership has a negative moderating effect on that relationship. That results wasaccordance with the Power Theory that the high institutional ownership may limit the amount of executive compensation.